2012
DOI: 10.1016/j.joca.2012.08.004
|View full text |Cite
|
Sign up to set email alerts
|

Body mass index affects knee joint mechanics during gait differently with and without moderate knee osteoarthritis

Abstract: Our results suggest that increased BMI is associated with different changes in biomechanical patterns of the knee joint during gait depending on the presence of moderate knee OA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
49
0
6

Year Published

2013
2013
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 83 publications
(58 citation statements)
references
References 45 publications
3
49
0
6
Order By: Relevance
“…Further, previous findings of changes in gait patterns (3,24) and coactivation/elongation of the hamstrings (25) suggest that KOA may not only affect the quadriceps, but also other thigh muscles, specifically the hamstrings. Some studies also reported flexor strength (1) and/or the extensor:flexor strength ratio to be reduced in osteoarthritic knees (26).…”
Section: Introductionmentioning
confidence: 83%
“…Further, previous findings of changes in gait patterns (3,24) and coactivation/elongation of the hamstrings (25) suggest that KOA may not only affect the quadriceps, but also other thigh muscles, specifically the hamstrings. Some studies also reported flexor strength (1) and/or the extensor:flexor strength ratio to be reduced in osteoarthritic knees (26).…”
Section: Introductionmentioning
confidence: 83%
“…Хотя непродолжительного уменьшения массы тела можно добиться с помощью диеты и физической нагрузки, сохранить полученный результат в течение длительного времени не удается большинству людей [96]. До 75% паци-ентов, соблюдающих диету (особенно очень низкокало-рийную -около 400-800 ккал/сут), набирают большую часть от потерянного в течение 1 года [55,80].…”
Section: лечение ожирения у больных остеоартрозомunclassified
“…Low muscle strength and power is associated with patients' poor mobility [17] and decreased knee range of motion (ROM) affect patients' ambulation function [32]. According to this the gait parameters are affected in patients with knee OA before and after total knee arthroplasty (TKA) [13].…”
Section: Introductionmentioning
confidence: 99%